Anthologies of historiographical speeches from antiquity to early modern times : rearranging the tesserae - Iglesias Zoido, Juan Carlos.; Pineda, Victoria. (International Studies in the History of Rhetoric, 2017)
Anthologies of speeches excerpted from history books constitute a relatively little-known rhetorical and bibliographic genre. From ancient times to the present day, the practice of culling characters' orations from one or more works and publishing them independently of their original source has produced new and different ways of reading and using history. Anthologies of Historiographical Speeches offers an introduction to the very diverse questions that arise from the study of the genre through a variety of approaches and methodological tools. Lying at the point where rhetoric and historiography intersect, the essays included in this volume focus on the rhetorical aspects of the collections, as well as on their production, transmission, and reception from antiquity to the early modern period.